Modèle numérique de clapage: Phase de chute - Farout-Fréson, Isabelle; Lefrançois, Emmanuel; Dhatt, Gouri; Sergent, Philippe (European Journal of Computational Mechanics, 2007)
We are interested here in the mixture composed of incompressible fluid and a certain mass of fluidised solid. The proposed model is based on the averaged form of the hydrodynamic biphasic equations, associated with a sediment transport equation with a specific numerical settling velocity sf w adapted for the dumped dredged material case. Both models (hydrodynamics and transport) are coupled considering the variation of density with a forward scheme. Calibrated on the convective descent on three experimental campaigns in canal of dumping of dredged materials, the model gives a very good agreement of convective descent with almost twenty experiments for materials 100% sand, 100% silt or mixture sand/silt without or with a horizontally ambient current (Villaret et al., 1997; Boutin 1999).